2021
DOI: 10.14412/1996-7012-2021-3-50-56
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of 23-valent polysaccharide pneumococcal vaccine in patients with systemic lupus erythematosus

Abstract: Objective: to study the safety and efficacy of the 23-valent polysaccharide pneumococcal vaccine (PPV-23) in patients with systemic lupus erythematosus (SLE).Patients and methods. The study included 75 patients with definite diagnosis of SLE at the age of 19–68 years, 10 (13%) of them had high SLE activity, 18 (24%) – moderate, 42 (56%) – low, in 5 (7%) patients the disease was in remission. PPV-23 was injected subcutaneously in a single dose of 0.5 ml. In 60 patients the follow-up period was ≥12 months, in 15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
(17 reference statements)
0
1
0
Order By: Relevance
“…SLE patients are at risk of invasive pneumococcal infections [48,49], but patients identify concerns about disease flares or side effects as barriers to receiving pneumococcal vaccinations [50]. Although limited, a study of PPSV23 vaccination in 75 SLE patients, including 13% with severe SLE, reported no disease exacerbations and lower rates of respiratory illness [51]. While a single dose of PCV20 may decrease the complexity of pneumococcal vaccination, there are currently no safety or immunogenicity studies of PCV20 in SLE patients.…”
Section: Special Implications Of Pneumococcal Vaccination In Systemic...mentioning
confidence: 99%
“…SLE patients are at risk of invasive pneumococcal infections [48,49], but patients identify concerns about disease flares or side effects as barriers to receiving pneumococcal vaccinations [50]. Although limited, a study of PPSV23 vaccination in 75 SLE patients, including 13% with severe SLE, reported no disease exacerbations and lower rates of respiratory illness [51]. While a single dose of PCV20 may decrease the complexity of pneumococcal vaccination, there are currently no safety or immunogenicity studies of PCV20 in SLE patients.…”
Section: Special Implications Of Pneumococcal Vaccination In Systemic...mentioning
confidence: 99%